Modelling water scarcity for policy adaptation to future droughts under various stresses (case study: Delfan plain). (2018) - Pourhaghi, Amir; Solgi, Abazar; Albaji, Mohammad; Zoratipour, Elahe
This study investigated the effect of management practices on the status of the aquifer using the finite difference method. Modelling was done with 60 cycles of stress using MODFLOW Model for a five-year period (60 months). The calibration was done in October, 2007 because of fewer fluctuations of groundwater level as the stable state. The state of the aquifer for November 2014 to November 2024 was predicted. In order to predict the future status of the aquifer, two options (i. to continue the current trend of exploitation and ii. 20% reduction of exploitation in drought condition) were performed and the model was run again for the next ten years. Running the model under drought condition indicates that groundwater level decreases with the average of (–7.80 m) in the following ten years, and 20% reduction in exploitation from the aquifer can somewhat improve the water level.